2016
DOI: 10.1097/eja.0000000000000252
|View full text |Cite
|
Sign up to set email alerts
|

Survival after long-term isoflurane sedation as opposed to intravenous sedation in critically ill surgical patients

Abstract: Compared with propofol/midazolam sedation, long-term sedation with isoflurane seems to be well tolerated in this group of critically ill patients after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 33 publications
2
32
0
5
Order By: Relevance
“…Sevoflurane, but not isoflurane, was found to increase blood-brain barrier permeability in old rats, promoting extravasation of immunoglobulin G with a selective affinity for pyramidal neurons [41]. The clinical utility remains debatable; long-term sedation with isoflurane was well tolerated in a retrospective analysis and associated with a higher 365-d survival (not delirium) compared with propofol/midazolam sedation [42].…”
Section: Psychomotoric Subtypes Of Deliriummentioning
confidence: 93%
“…Sevoflurane, but not isoflurane, was found to increase blood-brain barrier permeability in old rats, promoting extravasation of immunoglobulin G with a selective affinity for pyramidal neurons [41]. The clinical utility remains debatable; long-term sedation with isoflurane was well tolerated in a retrospective analysis and associated with a higher 365-d survival (not delirium) compared with propofol/midazolam sedation [42].…”
Section: Psychomotoric Subtypes Of Deliriummentioning
confidence: 93%
“…Recently, a number of trials have demonstrated the safety of long-time lower doses of isoflurane for ICU sedation. [1819] The above statements supported the protective effects on sepsis by the 0.5 MAC isoflurane in 60% oxygen which would be a good therapy for sepsis with improved clinical safety and broader clinical applications. However, the mechanism regarding the interaction between oxygen and isoflurane remains to be further studied.…”
Section: Discussionmentioning
confidence: 75%
“…The previous studies have reported that both hyperoxia[891011] and anesthetic dose isoflurane[121314] have significant protective effects on complex inflammation-mediated conditions including sepsis in various animal models of inflammation, and their application to the patients with critical diseases is limited because the use of anesthetic dose isoflurane in critically ill patients may have serious adverse consequences. [151617] A large number of trials have demonstrated the safety of long-time lower doses of isoflurane for ICU sedation,[1819] and long-term hyperoxia treatment can induce oxygen toxicity associated with the overproduction of reactive oxygen species (ROS). [20212223] Here, we demonstrated that combined administration of a low-dose isoflurane (0.5 minimum alveolar concentration [MAC]) with 60% oxygen reduced inflammatory responses to sepsis in animals and human peripheral blood mononuclear cells (PBMCs) and increased the 7-day survival rate of animals with experimental sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…A similar reduction in pulmonary complications has been demonstrated in a recent meta-analysis showing that volatile as opposed to intravenous anesthesia is associated with a significant reduction in overall mortality for cardiac surgical patients [11]. Although specific prospective data regarding the use of inhaled sedation in the ICU to prevent or treat lung injury is lacking, retrospective analysis of patients receiving inhaled sedation suggests an association between its use and reductions in 1-year and in-hospital mortality, perhaps related to a significant increase in ventilator-free days compared to sedation with intravenous agents [12]. …”
Section: Human Datamentioning
confidence: 99%